2020
DOI: 10.1136/bmjopen-2020-040644
|View full text |Cite
|
Sign up to set email alerts
|

Currently prescribed drugs in the UK that could upregulate or downregulate ACE2 in COVID-19 disease: a systematic review

Abstract: ObjectiveTo review evidence on routinely prescribed drugs in the UK that could upregulate or downregulate ACE2 and potentially affect COVID-19 disease.DesignSystematic review.Data sourceMEDLINE, EMBASE, CINAHL, the Cochrane Library and Web of Science.Study selectionAny design with animal or human models examining a currently prescribed UK drug compared with a control, placebo or sham group, and reporting an effect on ACE2 level, activity or gene expression.Data extraction and synthesisMEDLINE, EMBASE, CINAHL, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 117 publications
0
22
1
2
Order By: Relevance
“…Similarly, higher expression of ACE2 was also found among the Insulin administered animal models. Miller HD, et al has described the relationship between ACE2 upregulation and administration of glucagon-like peptide 1 (GLP) agonist or dipeptidyl peptidase-4 (DPP) inhibitors to treat diabetes ( Dambha-Miller et al 2020 ). Further, type 2 antidiabetic drug thiazolidinedione was also reported to up-regulate ACE2 expression In vivo and In vitro models ( Dambha-Miller et al 2020 ).…”
Section: Acei and Arbs Association With The Ace2 Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, higher expression of ACE2 was also found among the Insulin administered animal models. Miller HD, et al has described the relationship between ACE2 upregulation and administration of glucagon-like peptide 1 (GLP) agonist or dipeptidyl peptidase-4 (DPP) inhibitors to treat diabetes ( Dambha-Miller et al 2020 ). Further, type 2 antidiabetic drug thiazolidinedione was also reported to up-regulate ACE2 expression In vivo and In vitro models ( Dambha-Miller et al 2020 ).…”
Section: Acei and Arbs Association With The Ace2 Overexpressionmentioning
confidence: 99%
“…Miller HD, et al has described the relationship between ACE2 upregulation and administration of glucagon-like peptide 1 (GLP) agonist or dipeptidyl peptidase-4 (DPP) inhibitors to treat diabetes ( Dambha-Miller et al 2020 ). Further, type 2 antidiabetic drug thiazolidinedione was also reported to up-regulate ACE2 expression In vivo and In vitro models ( Dambha-Miller et al 2020 ). Thiazolidinediones improve vasodilation in diabetic patients by regulating the signaling cascade linking peroxisome proliferator-activated receptor-gamma ( ) and Renin-Angiotensin System ( Sarafidis et al 2004 ; Pal and Bhadada, 2020 ).…”
Section: Acei and Arbs Association With The Ace2 Overexpressionmentioning
confidence: 99%
“…The ACE2 enzyme has been identified to be the binding site of SARS-CoV-2 virus and controversy rose if the RAS system could be a therapeutic target, as an option to treat the disease by blocking the binding [ 14 ]. Recent findings have shown that ARBs have protective effects in hypertensive patients infected by SARS-CoV-2 [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. This article elaborates on the mechanism which triggers the hypertensive activity of angiotensin II and on the idea of considering ARBs as a tentative treatment for SARS-CoV-2 infections.…”
Section: Perspectives Of Arbs In Covid-19 Therapymentioning
confidence: 99%
“…The in silico studies suggest that losartan and ARBs are a promising COVID-19 treatment. Previous clinical studies indicate a safe and protective role of the RAS inhibitors [ 57 , 58 ].…”
Section: Perspectives Of Arbs In Covid-19 Therapymentioning
confidence: 99%
“…Data about medication before hospital admission are lacking, thus no information can be obtained whether specific drugs render the patients more prone to a severe course of the disease. This issue, relating angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, and statins has been extensively discussed in the meantime (13,14).…”
Section: Missing Baseline Informationmentioning
confidence: 99%